Eksplorasi Fungsi dan Nilai Kearifan Lokal Dalam Tindak Tutur Melarang di Kalangan Penutur Bahasa Jawa Dialek Standar - FX Samingin; Rangga Asmara (Universitas Tidar, 2016)
This research aimed at (1) identifying the realization of prohibition utterances and (2) exploring the local wisdom functions and values in the form of prohibiting utterances. In this research, I used pragmatic approach. The data used in this research were prohibition utterances consisting local wisdom values done by standard Javanese dialect speaker (2) and the reseponses to the functions and meaning of the utterances. The subject of the study were Javanese speakers in Solo, Yogyakarta, and Magelang. The instruments were (1) the observation manual and interview manual. The spoken utterances were collected by metode simak dan metode cakap as well as teknik dasar sadap, pancing, dan teknik lanjutan simak libat cakap, teknik rekam, dan teknik catat. In analysing the data, I used metode padan dan metode agih. Thus, the realisation of prohibition utterances was found in the two forms including prohibition utterances with its consequences and prohibition utterances with non consequences. In constructing utterances, the Javanese speakers use phatic marker such as oalah, eh, loh, wah, hus to limit and affirm the meaning of the utterances. The realization of the Javanese prohibition utterances were delivered in ngoko form. This is because its functions as advices from elderly to young people. The speech acts uttered by Javanese were (1) as a form of local wisdom of the speakers and (2) as the form of preserving Javanese language and culture. Keywords: Prohibition utterances, language function, local wisdom value, Javanese language